The Multifaceted Actions of CD73 During Development and Suppressive Actions of Regulatory T Cells - Da, Meihong; Chen, Luxia; Enk, Alexander; Ring, Sabine; Mahnke, Karsten (Frontiers in Immunology, 2022)
Adenosine (Ado) has been shown to have immunosuppressive effects in a variety of diseases. It can either be released directly into the extracellular environment by cells, or it can be produced by degradation of ATP within the extracellular spaces. This extracellular pathway is facilitated by the concerted actions of the ectoenzymes CD39 and CD73. In a first step CD39 dephosphorylates ATP to ADP and AMP, respectively, and in a second step CD73 converts AMP to Ado. Thus, activity of CD73 on the cell surface of cells is the rate limiting step in the generation of extracellular Ado. Among T cells, CD73 is most abundantly expressed by regulatory T cells (Tregs) and is even upregulated after their activation. Functionally, the generation of Ado by CD73+ Tregs has been shown to play a role in immune suppression of dendritic cells, monocytes and T cells, The expression of CD73 by Tregs in immunosuppressive environments, such as tumors, made CD73 a novel immune checkpoint. Therefore, therapeutical intervention by anti-CD73 antibodies or by chemical inhibitors of the enzymatic function is currently under investigation in preclinical models and in clinical trials. In the following, we summarize the expression pattern and the possible functions of CD73 in T cells and Tregs, and exemplify novel ways to manipulate CD73 functions to stimulate anti-tumor immunity.